The Effect Of Company Size, Public Accounting Firm Size, And Audit Tenure On Audit Report Lag With Auditor Industry Specialization As A Moderating Variable - Carisa Dea Ananda; Dirvi Surya Abbas; Imam Hidayat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The number of days that elapse between the closing date and the date on which the auditor's report about the company's annual financial statements is disclosed is the formula for audit report lag, which is the time it takes to complete audit reports. In terms of numbers, the audit report lag is measured in days. The purpose of this research is to investigate the relationship between auditor industry specialization and audit report latency, as well as the effects of auditor tenure, firm size, and the size of public accounting firms. Using a purposive selection approach, 71 firms were selected for the study's sample from the population of manufacturing enterprises listed on the Indonesia Stock Exchange between 2019 and 2023. For this data analysis, we flipped to Moderated Regression Analysis (MRA). The results showed that firm size had a negative effect on audit report lag, business size had a favorable effect, and public accounting firm size had no effect. Although auditor sector specialization can lessen the influence of business size on audit report delay, it cannot offset the impact of public accounting firm size and audit duration in general.